2016
DOI: 10.1097/shk.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment with Sodium Hydrosulfide Improves Regional Blood Flow and Alleviates Cecal Ligation and Puncture (CLP)-Induced Septic Shock

Abstract: Cecal ligation and puncture (CLP) induced sepsis is a serious medical condition, caused by a severe systemic infection resulting in a systemic inflammatory response. Recent studies have suggested the therapeutic potential of donors of hydrogen sulfide (H2S), a novel endogenous gasotransmitter and biological mediator in various diseases. The aim of the present study was to assess the effect of H2S supplementation in sepsis, with special reference to its effect on the modulation of regional blood flow. We infuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
5
24
1
Order By: Relevance
“…As already mentioned in the 'Introduction', the current body of literature on endotoxemia, endotoxin shock, sepsis, as well as various other forms of critical illness (e.g., burn injury, ARDS and hemorrhagic shock) is fairly controversial with respect to the role of H 2 S in the pathogenesis of these diseases; some of the studies have demonstrated that pharmacological H 2 S donation is beneficial in some experimental models (1116), while other studies have concluded that pharmacological inhibitors of H 2 S biosynthesis (1721), or the genetic deletion of CSE (22,23) is beneficial. Moreover, there are also studies demonstrating that H 2 S donation can be detrimental (1820), and there are even studies demonstrating that pharmacological inhibitors of H 2 S biosynthesis can be detrimental in certain models of critical illness (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned in the 'Introduction', the current body of literature on endotoxemia, endotoxin shock, sepsis, as well as various other forms of critical illness (e.g., burn injury, ARDS and hemorrhagic shock) is fairly controversial with respect to the role of H 2 S in the pathogenesis of these diseases; some of the studies have demonstrated that pharmacological H 2 S donation is beneficial in some experimental models (1116), while other studies have concluded that pharmacological inhibitors of H 2 S biosynthesis (1721), or the genetic deletion of CSE (22,23) is beneficial. Moreover, there are also studies demonstrating that H 2 S donation can be detrimental (1820), and there are even studies demonstrating that pharmacological inhibitors of H 2 S biosynthesis can be detrimental in certain models of critical illness (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the therapeutic effect of H 2 S donation in various models of circulatory shock (1116), while others have reported that the pharmacological inhibition of H 2 S production (1721) or the genetic deficiency of H 2 S-producing enzymes (22,23) results in beneficial effects.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S exerts broad range of physiological effects as an antioxidant, cytoprotective agent [1,2], vasorelaxant [35], neurotransmitter [6,7], and endogenous promoter of angiogenesis [8,9]. H 2 S also plays important roles in the regulation of various inflammatory processes via a variety of mechanisms including the regulation of pro-inflammatory signaling [1013]. Furthermore, H 2 S plays a role in the control of metabolism, via the regulation of glucose and lipid metabolism, insulin sensitivity and energy balance [1416].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the increased H 2 S circulation detected in the burn injury [36] and its levels correlated with inflammatory and clinical indices in rheumatoid arthritis patients [37]. Moreover, multiple lines of studies, in multiple experimental models, showing that therapeutic elevation of H 2 S concentrations or H 2 S donors can exert anti-inflammation and decrease the mortality caused by endotoxemia [38][39][40]. We found that CSE expression was significantly increased in LPS-induced macrophage, which were accompanied by increased inflammatory mediators and inflammatory cytokines production.…”
Section: Figmentioning
confidence: 99%